Role and place of the National Bank of Ukraine in Ukraineʼs accession to the EU and the Eurozone: Experience of central banks of EU countries - А. Tsvyetkov (Юридичний часопис Національної академії внутрішніх справ)
In this study, the role and place of the National Bank of Ukraine in the context of the countryʼs integration into the European Union and possible entry into the Eurozone are investigated. The experience of the central banks of European Union countries that have adapted to the requirements of the European System of Central Banks and the European Central Bank was analysed. The purpose of the research was to study the issues of harmonisation of legislation, monetary policy, financial stability, institutional independence and macroeconomic convergence. The study outlined the main stages that the central banks of the European Union member states went through before and after joining the Eurozone, as well as the challenges they faced during this process. Particular attention was paid to the role of the National Bank of Ukraine in preparing for the implementation of the Copenhagen criteria and integration. The study identified key areas for reforming the legal regulation of the Ukrainian banking system to ensure effective implementation of European monetary policy requirements: strategic priorities that the National Bank of Ukraine should take into account to maintain macroeconomic stability and convergence with the Eurozone. The paper emphasised the importance of the National Bank of Ukraineʼs institutional independence, coordination with fiscal authorities, and transparency in decision-making. It was argued that the experience of Central and Eastern European countries is an important benchmark for Ukraine, as it allows avoiding mistakes and implementing effective reforms. The study provided recommendations on the role of the National Bank of Ukraine in ensuring economic stability, creating conditions for sustainable growth, and approximation to European Union standards